Buerger's Disease (Thromboangiitis Obliterans): a Diagnostic Challenge - Jorge, VC (2011)
Buerger's disease or Thromboangiitis obliterans is a segmental inflammatory disease that affects the vessels and nerves of the extremities. It usually affects men below 45 years old and correlates with tobacco, as a predisposing factor. The authors present the case of a 34-year-old male, with ulcers in the fingertips with progressive worsening: acrocyanosis, slow healing, necrosis and finally loss of substance. Dorsalis pedis and posterior tibial pulses were not palpable. Personal history of heavy smoking was (20 pack-years). The angiography revealed proximal occlusion of the left posterior tibial and interosseal arteries, with distal circulation by the anterior tibial artery. He was submitted to disarticulation of the second left toe and therapy with pentoxifyline and iloprost infusion, calcium antagonist, antiplatelet drugs, statin and low molecular weight heparin (later replaced by oral anticoagulation). Improvement was seen of active vascular lesions and pain symptoms.